2009
DOI: 10.1007/s00784-009-0330-0
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress in myofascial pain patients

Abstract: Although myofascial pain has often been described as being associated with psychosocial stress, detailed evidence in support of this assumption, either from standardized clinical examination or from validated chronic stress questionnaires, is absent. The hypothesis of the present study was that some stressors lead to higher scores in patients suffering from chronic myofascial pain than in pain-free controls and in patients suffering from chronic facial pain. One hundred and fifty subjects were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
1
10
0
6
Order By: Relevance
“…The mean pain intensity in the patient group was approximately 4.9 on the NRS. This is comparable with results obtained in a previous study that assessed pain intensity among TMD patients by the use of the GCPS [36]. In this study, subjects with GCPS >2 were excluded, because these patients have been shown to suffer from psychosocial dysfunction, including elevated depression and somatization scores [37].…”
Section: Discussionsupporting
confidence: 63%
“…The mean pain intensity in the patient group was approximately 4.9 on the NRS. This is comparable with results obtained in a previous study that assessed pain intensity among TMD patients by the use of the GCPS [36]. In this study, subjects with GCPS >2 were excluded, because these patients have been shown to suffer from psychosocial dysfunction, including elevated depression and somatization scores [37].…”
Section: Discussionsupporting
confidence: 63%
“…It is known that elevated levels of psychological stress have the potential to intensify perceived pain, reduce an individual's capacity to tolerate pain and affect overall well‐being . This is particularly applicable for chronic myofascial pain which in several studies have been strongly associated with stress in addition to other psychological aspects . Although several studies have assessed the relationship between chronic OP and stress, no study has taken into account patients with acute OP.…”
Section: Discussionmentioning
confidence: 99%
“…30 Pain patients frequently fear isolation, estrangement from others, and may have a general sense of feeling like an outcast. 31 Also, financial burdens and family role changes are common stressors. In deciding whether to treat anxiety, the patient's subjective level of distress is the primary impetus for the initiation of treatment.…”
Section: Common Mental Health Issues Related To Chronic Pain Anxietymentioning
confidence: 99%